2015
DOI: 10.1016/j.jocd.2014.11.002
|View full text |Cite
|
Sign up to set email alerts
|

Insights Into Relationships Between Body Mass, Composition and Bone: Findings in Elite Rugby Players

Abstract: Recent reports indicate that bone strength is not proportional to body weight in obese populations.Elite rugby players have a similar body mass index (BMI) to obese individuals, but differ markedly with low body fat, high lean mass and frequent skeletal exposure to loading through weight-bearing exercise. The purpose of this study was to determine relationships between body weight, composition and bone strength in male rugby players characterised by high BMI and high lean mass.Fifty two elite male rugby player… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 24 publications
0
18
1
Order By: Relevance
“…In another study, nearly 50% of men and women classified as obese using densitometric methods were determined to be of normal BMI (33). Athletes who build high levels of muscle (lean body) mass often possess BMI levels above 30 and would be inappropriately classified as obese (34). However, when they retire, many will increase their body fat levels substantially, while maintaining their high BMI.…”
Section: Problems With Bmi As a Measure Of Obesitymentioning
confidence: 99%
“…In another study, nearly 50% of men and women classified as obese using densitometric methods were determined to be of normal BMI (33). Athletes who build high levels of muscle (lean body) mass often possess BMI levels above 30 and would be inappropriately classified as obese (34). However, when they retire, many will increase their body fat levels substantially, while maintaining their high BMI.…”
Section: Problems With Bmi As a Measure Of Obesitymentioning
confidence: 99%
“…Of all fields, sports science and medicine has witnessed a considerable rise in the number of published research studies utilising DXA for the assessment of total and regional body composition. These studies have included the body composition profiling of competitive athletes [3,4], and in relation to bone density [5][6][7] and nutritional status [8,9]. Serial DXA measurements are increasingly being used to explore the effects of training and diet on athlete body composition changes [10][11][12][13][14][15][16][17].…”
Section: Introductionmentioning
confidence: 99%
“…The high proportion of patients classified as overweight-obese (68.8%) by the BMI method in the present study is a reflection of the sports commonly played by our patient population, in particularly rugby and Australian rules football where larger body frames are advantageous with high contact play. 21 Post-hoc analysis of the IKDC scores revealed that Cluster 4, the subgroup with the highest overall health and knee function scores, reported the ability to perform a higher level of activity without experiencing instability, at a higher than expected rate compared with Cluster 1. These findings highlight the need to clearly establish the reasons why patients decide to undergo ACL reconstruction.…”
Section: Discussionmentioning
confidence: 88%